Physical activity promotion: precise matching of message frames and affect types. Issue 1 (2nd January 2021) - Li, Kin-Kit; Lee, Candy H.-Y.
Abstract: Objective: Matching between affect orientations and message frames have been shown to enhance the persuasiveness of health messages. Based on a two-dimensional regulatory model (direction: approach/avoidance, valence: appetitive/aversive), this study examined whether a precise matching between affect and message frame would enhance physical activity (PA) attitudes, intentions, and behaviours. Design: Using a 2 (gain/loss frames) x 2 (positive/negative end-states) design, 147 college students were randomly assigned to one message-frame condition (gain-positive, gain-negative, loss-positive, or loss-negative). Four identified affect types (approach-positive, approach-negative, avoidance-positive, and avoidance-negative) were considered as matched, respectively, with the four message-frame conditions. The participants were subsequently grouped into fully-matched, direction-matched only, valence-matched only, or unmatched. Main Outcome Measures: The immediate PA attitude and intention after the experiment and the PA attitudes, intentions, and behaviours at a two-week follow-up were reported. Results: Post-manipulation and follow-up intentions were greater in the fully-matched as compared with the unmatched group. Follow-up physical activity was more in the valence-matched than the unmatched group. No other differences were found across the matching types. Conclusion: Findings partially supported the importance of a precise matching between affect orientations and message frames. The affect types may characterize an individual's sensitivity towards the corresponding regulatory information.